Cover Image Volume 48, Issue 8. (5th July 2018) - Dautov, Rustem; Distefano, Salvatore; Bruneo, Dario; Longo, Francesco; Merlino, Giovanni; Puliafito, Antonio; Buyya, Rajkumar
Abstract : The cover image, by Rustem Dautov et al., is based on the Research Article Metropolitan Intelligent Surveillance Systems for Urban Areas by Harnessing IoT and Edge Computing Paradigms, https://doi.org/10.1002/spe.2586 . Photo Credit: Rustem Dautov.